Effect Of Free Cash Flow And Leverage On Sticky Cost Behavior In Food And Beverage Companies Listed On The Idx In 2018-2022 - Nurlina, Nurlina; Mira, Mira; Firman Syah (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to determine the effect of free cash flow and leverage on sticky cost behavior in food and beverage companies listed on the IDX in 2018-2022. The type of data used in this study is quantitative data obtained from financial statements. Data collection is carried out by accessing the official website of the Indonesia Stock Exchange. In this study, the data source used is secondary data. The research instruments used in this study use the documentation method. The results of the study using statistical calculations through the eviews version 12 application regarding the influence of free cash flow and leverage on sticky cost behavior, the author draws the conclusion that free cash flow has an effect on sticky cost behavior while leverage has no effect on sticky cost behavior.